Tellurite Base Glasses – A Structural Study: Exploring the Potential Applications and Structural Characteristics of Tellurite Base Glasses (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Tellurite base glasses are most promising glasses now a day. Their potential applications in thefield of phonics, lasers ,optical amplifiers, LEDs, and other photonic devices attract researchers .Structural of tellurite with various glass formers is studied.